Chemistry of polyhalogenated nitrobutadienes, 14: Efficient synthesis of functionalized (Z)-2-allylidenethiazolidin-4-ones - Zapol’skii, Viktor A.; Namyslo, Jan C.; Gjikaj, Mimoza; Kaufmann, Dieter E. (Beilstein Journal of Organic Chemistry, 2014)
The reaction of mercaptoacetic acid esters with pentachloro-2-nitro-1,3-butadiene (1) provides an appropriate precursor for the synthesis of special thiazolidin-4-ones. Applying different anilines as the second constituent for the requisite cyclization step, a series of (Z)-2-allylidenethiazolidin-4-ones was obtained in yields up to 81%. Some subsequent reactions have been examined too, such as the formation of perfunctionalized 1H-pyrazoles upon treatment with hydrazine. Thiazolidinones are as well known for their physiological activities as for their application in optoelectronics.
Keywords: atropisomers; cyclization; 2-nitroperchlorobutadiene; 1H-pyrazoles; thiazolidin-4-ones